Tychonoff and connected products theorems are equivalent - Pérez, Juan Antonio (2017)
In Topology, Tychonoff’s theorem asserts that the compactness of a product of topological spaces and compactness of each of its factors are equivalent facts. Analogously, the connected products theorem does the same about connectedness. This note is devoted to prove the equivalence between thes two topological results.